The Proximate Composition, Mineral Element Contents and Physicochemical Properties of the Flower Oil of Aspilia africana (Pers.) C. D. Adams (Asteraceae) - Johnson, Ekarika; Etim, Emmanuel; Udoh, Anwanabasi; Eseyin, Olorunfemi (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
In a region like Africa and in an era where oil adulteration is commonplace coupled with prohibiting high cost of the available commercial oils, there is need to research for more sources of the commercial oils where quality can be guaranteed and the supplies regular. The flower oil of Aspilia africana which can be cheaply extracted from the flowering plant found in abundance everywhere in tropical Africa can solve this problem if its quality compares favourably with the available commercial oils. This work was undertaken to investigate the physicochemical properties of the oil extracted from the flower of Aspilia africana with the view of comparing its quality with some commercial vegetable oils and exploring its potentials as pharmaceutical base oil. The proximate composition, mineral element contents, physicochemical properties and the fatty acid composition of the flower oil obtained by soxhlet extraction using n-hexane were determined using standard methods and the results compared with those of some standard commercial oils. The physicochemical analysis gave comparable values of some parameters such as relative density, refractive index, optical rotation, viscosity, acid value, ester value, hydroxyl value and iodine value with those of some commercial vegetable oil. The GC-MS analysis showed the oil to contain high levels of unsaturated fatty acids (oleic acid, 59.07%). Proximate analysis of the oil showed that it contained 36.40% of carbohydrate, 22.35% of protein, 8.90% ash and 15.6% lipid. Iron and potassium had the highest concentrations as mineral elements. The characteristic properties of this oil suggested potential for its application as pharmaceutical oil that might satisfy some of the deficiencies of commercial vegetable oils.